CT reconstruction based 3D model of the digital cushion’s blood supply in the hind foot of an African savanna elephant (Loxodonta africana) - Reinitz, László Zoltán; Lenzing, Franka; Papp, Endre; Biácsi, Alexandra; Fajtai, Dániel; Petneházy, Örs (Frontiers in Veterinary Science, 2024)
Introduction Foot health is crucial for elephants, as pathological lesions of the feet are a leading cause of euthanasia in captive elephants, which are endangered species. Proper treatment of the feet, particularly in conditions affecting the digits and the digital cushion, requires a thorough understanding of the underlying anatomy. However, only limited literature exists due to the small population and the epidemiological foot diseases which often precludes many deceased elephants from scientific study. The aim of this study was to provide a detailed anatomical description of the blood supply to the African elephant's hindfoot. Methods The healthy right hindlimb of a nineteen-year-old deceased female African savanna elephant was examined using computed tomography. Following a native sequence, 48 ml of barium-based contrast agent was injected into the caudal and cranial tibial arteries, and a subsequent scan was performed. The images were processed with 3D Slicer software. Results The medial and lateral plantar arteries run in a symmetrical pattern. They each have a dorsal and a plantar branch, which reach the plantar skin before turning towards the axial plane of the sole to reach the digital cushion from the proximal direction. An accurate 3D model of the arteries and the bones of the foot, a set of labelled images and an animation of the blood supply have been created for ease of understanding. Discussion In contrast to domestic ungulates, the digital cushion of the hindlimb is supplied differently from that of the forelimb. The lack of large vessels in its deeper layers indicates a slow regeneration time. This novel anatomical information may be useful in the planning of surgical interventions and in emergency medical procedures.